Co-evaporated perovskite light-emitting transistor operating at room temperature - Klein, Maciej (2022)
Solution-processed hybrid organic–inorganic perovskite light-emitting transistors (PeLETs) suffer from low brightness and environmental instability induced by temperature-activated trapping, ionic motion, and polarization effects, which so far have been hindering the realization of devices operating at room temperature. Here high quality thermally co-evaporated methylammonium lead iodide perovskite films are employed to minimize ionic motion and significantly improve the electroluminescence characteristics of the perovskite active layer, enabling stable device operation up to ≈ 310 K. The demonstration of PeLETs operating at and beyond room-temperature paves the way for practical applications in the rapidly evolving area of solid-state lighting, active-matrix displays, and visible light communications.